Pulmonary Thromboembolism during Acetabular Fracture Operation - Il Seo; Chang-Wug Oh; Joon-Woo Kim; Kyeong-Hyun Park (Journal of Trauma and Injury)
Acetabular and Pelvic ring fractures are major high-energy trauma injuries and are often combined with other injuries. In particular, cause of long duration of immobilization and combined injuries, venous thromboembolism is a common complication in trauma patients with pelvic or acetabular fractures. We report a case of a fatal pulmonary thromboembolism during the acetabulum fracture operation in a 62-year-old male patient.